THE IMPACT OF LOW‐PRIORITY LAWS ON CRIMINAL ACTIVITY: EVIDENCE FROM CALIFORNIA. (9th May 2016) - Ross, Amanda; Walker, Anne
Abstract : We examine the impact of low‐priority initiatives on criminal activity. Low‐priority initiatives mandate that minor marijuana possession offenses be the lowest enforcement priority for police. Localities pass these laws because they believe if officers devote fewer resources toward minor marijuana crimes, more resources will be available to deter more serious crimes. Using data from California, we find that jurisdictions that adopted low‐priority laws experienced a reduction in arrests for misdemeanor marijuana offenses. However, we do not find evidence of a consistent effect of enacting a low‐priority initiative on the crime or clearance rate of other felonies. ( JEL H1, H4, K4)